A chapter called controversy: breaking down the Delhi high court appellate bench verdict in F Hoffmann-La Roche v Cipla Ltd. Issue 2 (April 2016) - Ghosh, Eashan
Abstract : On 27 November 2015, an appellate bench of the Delhi High Court in F Hoffmann-La Roche v Cipla Ltd issued a 184-paragraph opinion, overturning in part a 2012 single judge decision and holding that Cipla had infringed Roche's Indian patent over erlotinib hydrochloride. However, it turned out that large swathes of the appellate decision had been lifted verbatim from an article I co-authored for this journal in 2013. Alerted to the lapse, the bench issued a corrected order on 8 December 2015 and, in an unprecedented move, opted to expunge the plagiarized portions and issued an apology for the oversight. As a result, the rebooted ruling dives straight into the legal issues involved and, as this article posits, is no less explosive for its findings on merits than it was for the curious episode that created a buzz around it for all the wrong reasons. In doing so, the decision deviates from Indian precedent in a manner that could, in equal parts, be construed as path-breaking, unsettling and, above all, fiercely controversial.